Penerapan Metode Manhaji Karya Joko Nursiyo dalam Pembelajaran Nahwu Kelas Ix di Pondok Pesantren Miftahul Huda Putri Boyolali Tahun Ajaran 2021/2022 - Athif Azhari Adilah (Thulabuna: Jurnal Pendidikan Bahasa Arab, 2021)
This research is motivated by the issue that nahwu (Arabic grammar) is still often considered a boring and difficult subject to understand, including by students (santri) who study in Islamic boarding schools (pesantren). Even though Arabic is one of the flagship subjects taught in pesantren, this also applies at Pondok Pesantren Miftahul Huda Putri Boyolali. This study is a Classroom Action Research (CAR) focusing on the ninth-grade santri at Pondok Pesantren Miftahul Huda Putri Boyolali, involving a total of 64 students. The research results show that in Cycle I, the implementation of the Manhaji method by Joko Nursiyo in nahwu learning resulted in 45 students reaching the Minimum Mastery Criteria (KKM), while 19 students had not yet met the KKM. Meanwhile, in Cycle II, after applying the Manhaji method, 60 students were able to reach the KKM, and only 3 students still fell short; 1 student was absent due to illness. This illustrates that the application of the Manhaji method by Joko Nursiyo in teaching nahwu can improve the learning outcomes of the students. Therefore, it is recommended that teachers apply the Manhaji method in nahwu lessons to add variety to the existing teaching methods.